Volume 1A: Combustion, Fuels and Emissions 2013
DOI: 10.1115/gt2013-94363
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of a Premixed Turbulent Confined Jet Flame Using the Flamelet Generated Manifold Approach With Heat Loss Inclusion

Abstract: In the present paper a computational analysis of a confined premixed turbulent methane/air jet flame is presented. In this scope, chemistry is reduced by the use of the Flamelet Generated Manifold (FGM) method [1, 2], and the fluid flow is modeled in a RANS context. In the FGM technique the reaction progress of the flame is generally described by a few control variables, for which a transport equation is solved during runtime. The flamelet system is computed in a pre-processing stage, and a manifold with all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The burner is operated at ambient pressure with a mixture preheated up to 573 K. The same test case has been used for numerical validation by other authors and the main results are subsequently summarized. Donini et al [24] investigated the influence of heat loss using a FGM implementation in the commercial CFD code CFX in combination with a RANS approach. It was shown that for the current test case the addition of heat losses in the combustion model is essential to correctly predict the flame structure.…”
Section: Introductionmentioning
confidence: 99%
“…The burner is operated at ambient pressure with a mixture preheated up to 573 K. The same test case has been used for numerical validation by other authors and the main results are subsequently summarized. Donini et al [24] investigated the influence of heat loss using a FGM implementation in the commercial CFD code CFX in combination with a RANS approach. It was shown that for the current test case the addition of heat losses in the combustion model is essential to correctly predict the flame structure.…”
Section: Introductionmentioning
confidence: 99%
“…To this purpose a laminar flamelet database is generated from a one-dimensional (1D) flamelet calculation performed with full kinetics and detailed transport. The FGM technique has the admirable advantage of considerably reducing the computational cost of combustion simulations [1,2,8], while keeping the accuracy to high levels. A key advantage of FGM is in fact the capability to predict minor species in a consistent way.…”
Section: Fgmmentioning
confidence: 99%
“…A multiphysics simulation is here applied to a confined premixed swirling flame [18,19] whose stabilization has been shown to be sensitive to the wall conditions as in other similar flames [20][21][22][23]. The flame has previously been simulated successfully in a non-coupled and stand-alone LES based on a non-adiabatic F-TACLES (Filtered Tabulated Chemistry for LES) model [24].…”
Section: Introductionmentioning
confidence: 99%